Performance study of an OFDM visible light communication system based on white LED array - 田崇文 李艳婷 叶玮琳 全相印 宋占伟 郑传涛 (Optoelectronics letters, 2011)
By introducing orthogonal frequency division multiplexing （OFDM） technology, a visible light communication （VLC） system using a 5~5 white LED array is studied in this paper. The OFDM transmitter and receiver are modeled through MATLAB/Simulink tool. The electrical-optical-electrical （EOE） response of the VLC channel, which is also the re- sponse of the detector, is derived based on Lambert＇s lighting model. Then the modeling on the overall OFDM/VLC system is established by combining the above three models together. The effects of the factors which include the digital modulation, Reed-Solomon （RS） coding, pilot form, pilot ratio （PR） and communication distance on the bit error rate （BER） of the system are discussed. The results show that through the use of RS coding, block pilot, quad- rate phase shift keying （QPSK） modulation and a suitable pilot ratio about 1/3, under the communication rate about 550 kbit/s, the BER can be dropped to below 10^-5, and the communication distance can reach 0.9 m.